Análise de estabilidade de taludes rochosos na rodovia BR-392, Caçapava do Sul e São Sepé, RS - Vargas, Rodrigo Rockenbach (2022)
In highway engineering, excavations, cutting and remodeling of soil and/or rock slopes are frequently required in projects aimed at the construction of highways. This type of service requires attention to safety and stability conditions, since slopes susceptible to landslides carry a high risk to productive activities and human lives. The objective of this study was to carry out a geological-geotechnical analysis on two rocky slopes along the BR-392 highway, in the stretch that crosses the towns of Caçapava do Sul and São Sepé, to determine the conditions of stability and risk to mass movements that impact the flow of the highway and/or cause eventual accidents with human and economic damage. For these purposes, two aerophotogrammetric surveys were carried out with the aid of a Remotely Piloted Aircraft (RPA) in order to generate Virtual Outcrop Models (MVAs) to help guide the discontinuity plans of slopes 1 and 2. The characterization of the rocks and discontinuities that make up these slopes was carried out, regarding the types of rock and discontinuities, weathering conditions, spacing, persistence, filling and infiltration of discontinuities, in addition to parameters of surface roughness, rock resistance and definition of sets of plans. The orientation data of the discontinuities were represented in stereographic projections in order to carry out an analysis for the failure mechanisms: planar, wedge and tipping and to determine the potential failure models for each slope. With this, it was possible to estimate the factor of safety (FS) for each slope according to the types of failure identified. The factors obtained are all greater than one, which indicates stability, and only planar and wedge failure conditions were identified.